Distribution and flux of Pu-238, Pu-239,Pu-240, Am-241, Cs-137 and Pb-210 to high arctic lakes in the Thule district (Greenland) - Eriksson, M; Holm, Elis; Roos, P; Dahlgaard, H (Journal of Environmental Radioactivity, 2004)
Environmental samples (soil, sediment and lake water) in the Thule area (NW Greenland) have been studied to assess the contamination of radionuclides originating from a nuclear weapons accident (the Thule accident in 1968). Four lakes were chosen at different distances from the point of impact with the Thule air base community situated in between. The sedimentation rates in the lakes varied from 0.4 mm a(-1) (5 a a(-1) to 1.6 mm a(-1) (82 mg cm(-2) a(-1)). With these sedimentation rates, it is not possible to resolve the Pu-239,Pu-240 global fallout peak from a possible Pu-239,Pu-240 "accident" peak in the sediment depth profiles. However, the Pu-239,Pu-240/Cs-137 and the Pu-238/Pu-239,Pu-240 ratios agreed well with global fallout ratios, indicating that plutonium originating from the accident had not reached these lakes. This also indicates that the Thule air base community has probably only been exposed to radionuclides from the accident to a very limited extent. A limited study showed that Pb-210 could not be used as a normalizing nuclide to explain the transport of transuranic elements from the catchment area to the lake, i.e. Pb-210 has a different transport mechanism from that of the transuranic elements studied in this investigation.